Matching Local Network Structures and Local Needs Transforming Local Societies in Bamberg, Germany, Towards Climate Resilience - Neuner, Andreas; Jelinski, Sarah; Stadlmeier, Anna; Byron Walker, Blake; Kremer, Dominik (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
Climate change poses major challenges for landscapes regarding their resilience-inducing and health-promoting effects for the local population. Beyond losing just a familiar aesthetic quality, landscapes become restricted in their function as a place of recreation and recovery, social participation, and physical activity. In this context, the consequences of climate change increasingly affect population groups already limited in their daily access to health-promoting elements of landscapes. Translating supra-regional climate resilience frameworks for the needs of local populations, municipalities are assigned a key role. However, this complex process can only be addressed in cooperation with local politics, science, businesses, and civil society engagement. Corresponding structures still need to be established in many places. Their acceptance will largely depend on public participation processes and the implementation of their results by local politics. Drawing from a case study in Bamberg, Germany, we conducted 92 street interviews revealing the specific needs of local residents regarding their everyday well-being and resilience. In addition, following a mixed-method approach, we engaged in participant observation of the promising local network structures. As a result, we suggest further optimization of existing network structures to match the needs of the local population: Further establishing network structures, especially for the purpose of knowledge and practice transfer between different local groups and stakeholders. Establishing network structures for the practical transfer of simple and often profitable changes in everyday health practices of the local population. Training pioneers of change from different social backgrounds to act as representatives for their respective peer groups.